2002
DOI: 10.1258/13576330260440691
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac picture archiving and communication systems and telecardiology-technologies awaiting adoption

Abstract: Diagnostic and therapeutic procedures associated with cardiology are heavily supported by diagnostic imaging technology. The management of such images, including radiographs, echocardiography examinations and cardiac angiography studies, requires a suitable means of handling the data. A number of manufacturers are now offering picture archiving and communication systems (PACS) and telecardiology options. These could greatly improve the efficiency of data management for cardiac examinations, including linkage t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…Similar suggestions for multi-departmental PACS have been given in the literature (Bergh 2006;Crowe and Hailey 2002;Brennecke et al 1992). The implementation of a web-based multi-agent architecture proves that the introduction of common healthcare standard is beneficial to the exchange of health records among multiple patient repositories (Choe and Yoo 2008).…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Similar suggestions for multi-departmental PACS have been given in the literature (Bergh 2006;Crowe and Hailey 2002;Brennecke et al 1992). The implementation of a web-based multi-agent architecture proves that the introduction of common healthcare standard is beneficial to the exchange of health records among multiple patient repositories (Choe and Yoo 2008).…”
supporting
confidence: 62%
“…Having these strategic sakes, the implementation of the compartmental PACS at PolyU proved streamlined clinical dataflow with substantial cost reduction, effectively addressing the issues pointed out in the literature (Crowe and Hailey 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of the PACS has affected the work practices of many users, including radiologists, radiographers, nurses and doctors. A literature study [1][2][3][4][5][6][7] indicated that understanding work practice changes and clinicians' acceptance of the changes is critical for the successful integration of a PACS into clinicians' work practice. The rapid delivery of X-ray images to clinicians is critical for timely diagnoses and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Despite intensive research in this direction, theadoptionofsuch systems in everydayworkflowislimited [5,6],mainlydue to substantial difficulties in thei ntegrationo f services [7,8]. While expensived edicated data sharing systems are devoid of distrib-utingand integrating capabilities [9,10], the employmento fa lreadya vailable connections often suffers from inadequate bandwidth, thus precluding real-time imagesharing [11].Moreover, vendor-orplatform-dependent solutions resulti na dditional costs andl imited expandability [5,12].H ence, most of the current projects are based mainly on twos imple modes:" store and forward" and "real-time" videoconferencing [13].…”
Section: Introductionmentioning
confidence: 99%